Perancagan Sistem Informasi Pengelolaan Kas Berbasis Web Di Masjid Islamic Center Dato Tiro - Gusriandi Gusriandi; Dedy Hendryadi; Andi Nurul Faizah (Journal System Information And Computer, 2024)
Dato Tiro Islamic Center Mosque has not used information technology in the process of cash managemen and cash reporting process has not been extensive, the system what they apply is still using a cash management system. This research aims to: (1) know the development of Cash Management Information System web based at the Mosque Islamic Center Dato Tiro. (2) implementing a Web-Based Cash Management Information System at the Mosque Islamic Center Dato Tiro. The method used is the waterfall method, which is a model that provides systematic and sequential approaches for software developers, namely needs Analysis, System Design, Program Code Writing, Program Testing, Aplication and Implementation. The results of this study are: (1) The Islamic Center Dato Tiro Mosque’s cash management information system, in its design using the waterfall method which includes needs Analysis, System Design, Program Code Writing, Program Testing, Aplication and Implementation. The unified modeling language (UML) system design model is use case diagrams, activity diagrams and sequence diagrams, the programming language using PHP, MySQL as the database storage, testing is carried out using the black box method. (2) Testing uses the System Usability Scale method ( SUS) with a value of 70 which means grade scale B or included in the Good category, which means that the mosque's cash management information system is feasible to implemented and can be used easily by its users.